Psychosocial, Educational, and Economic Impacts of COVID-19 2023
DOI: 10.5772/intechopen.101677
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Perspectives on the Emergency Remote Assessment during the COVID-19 Pandemic

Abstract: The unprecedented health crisis triggered by the COVID-19 pandemic put on hold traditional educational practices. Emergency remote teaching was adopted as a response, with various degrees of success and satisfaction around the globe. This perspective chapter focuses on the remote emergency assessment as a measure to ensure the completion of the educational cycle for students caught in the 2020 crisis, after debates around the relevance and soundness of such activities both for students, and for society at larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In contrast, other studies found that through computer-assisted assessment technologies, students were able to actively participate in the assessment process during emergency remote learning (Cernicova-Buca, 2021;Seraj et al, 2022). Given that teachers in this study had limited technologically assisted assessment resources, it is not surprising that they were unable to engage students in a way that fosters students' metacognitive abilities and allows them to monitor their own learning.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In contrast, other studies found that through computer-assisted assessment technologies, students were able to actively participate in the assessment process during emergency remote learning (Cernicova-Buca, 2021;Seraj et al, 2022). Given that teachers in this study had limited technologically assisted assessment resources, it is not surprising that they were unable to engage students in a way that fosters students' metacognitive abilities and allows them to monitor their own learning.…”
Section: Discussionmentioning
confidence: 62%
“…The need to involve students in remote assessment has been confirmed by Cernicova-Buca (2021) and Seraj et al (2022). Cervicova-Buca, in his research, emphasized the use of computerassisted assessment technologies that encourage student self-and peer assessment.…”
Section: Literature Reviewmentioning
confidence: 99%